The Body Mass Index Towards Physical Fitness in Pencak Silat Athletes - Jalil, Rasyidah; Hasanuddin, Muh Iqbal; Kahar, Irsan; Yuni, Yuni; Kardi, Ipa Sari; Ibrahim, Ibrahim; Alimuddin, Alimuddin (Department of Physical Education, Sport, Health and Recreation, 2022)
The purpose of the study is to determine whether there is a contribution of body mass index towards physical fitness in pencak silat athletes in Palopo City. This is a quantitative descriptive research. The independent variable is body mass index and the dependent variable is physical fitness. The population in this study is the pencak silat athletes inPalopo city. The number of populations are 15 athletes. Sampling technique was saturated sample technique, where all members of the population become sample. The sample in this study are 15 athletes. The data analysis techniques used were descriptive techniques, categorization, data normality, correlation and regression tests using the SPSS program. The results of this study suggest that: The level of body mass index of pencak silat athletes in Palopo City is in the normal category which is 93%. The level of physical fitness of the o pencak silat athletes in Palopo is in the good category at 73%. There is a significant contribution of body mass index to physical fitness in pencak silat athletes in Palopo City which is 64.5%.